Effects of Dexamethasone Intravitreal Implant on Multifocal Electroretinography in Diabetic Macular Oedema - Tranos P; Koukoula S; de Politis PB; Tranou M; Giamouridou O; Stavrakas P; Panos GD (Drug Design, Development and Therapy)
Paris Tranos,1 Stavrenia Koukoula,1 Penelope Burle de Politis,1 Marianna Tranou,1 Olympia Giamouridou,1 Panagiotis Stavrakas,2 Georgios D Panos3– 5 1Vitreoretinal Department, Ophthalmica Eye Institute, Thessaloniki, Greece; 2Department of Ophthalmology, School of Medicine, University of Patras, Patras, Greece; 3Division of Ophthalmology and Visual Sciences, School of Medicine, University of Nottingham, Nottingham, UK; 4Department of Ophthalmology, Queen’s Medical Centre, Nottingham University Hospitals, Nottingham, UK; 5First Department of Ophthalmology, AHEPA University Hospital, School of Medicine, Aristotle University of Thessaloniki, Thessaloniki, GreeceCorrespondence: Georgios D Panos, Department of Ophthalmology, Queen’s Medical Centre, Derby Road, Lenton, Nottingham, NG7 2UH, UK, Tel +44 115 924 9924, Email gdpanos@gmail.comPurpose: To evaluate the efficacy of the dexamethasone implant on the electrophysiological profile of Diabetic Macular Oedema (DMO) patients over six months.Methods: In this prospective, single-center study 30 eyes of 22 patients were examined using comprehensive baseline assessments including best-corrected visual acuity (BCVA), central retinal thickness (CRT), contrast sensitivity (CS) and multifocal electroretinogram (mfERG), before and after 0.7mg dexamethasone implant injection, with follow-ups at months 1, 2, 4, and 6. The study employed mixed models to analyse within-subject and between-subject correlations, considering the complexities of multiple measurements per subject.Results: At baseline, BCVA was 0.66 ± 0.104 logMAR, improving to 0.568 ± 0.104 logMAR by month 6 (P > 0.05). CRT significantly reduced from 521 ± 28.7 μm to 336 ± 28.7 μm (P < 0.05). CS slightly increased from 26.8 ± 1.23 letters to 28.5 ± 1.05 letters (P > 0.05). P wave amplitude saw a notable rise from 33.4 ± 5.66 μV to 47.9 ± 5.43 μV (P < 0.05). P wave implicit time changed minimally from 47.4 ± 0.503 seconds to 48.0 ± 0.503 seconds (P > 0.05). No severe adverse events were recorded.Conclusion: These results underscore the 0.7mg dexamethasone implant’s potential in improving certain electrophysiological markers in DMO, while also highlighting the need for further investigation into its comprehensive impact on retinal function.Keywords: dexamethasone implant, electroretinogram, diabetic macular oedema, visual function, macular thickness, visual acuity, contrast sensitivity